Galactofuranose in Mycoplasma mycoides is important for membrane integrity and conceals adhesins but does not contribute to serum resistance. Issue 1 (14th October 2015) - Schieck, Elise; Lartigue, Carole; Frey, Joachim; Vozza, Nicolas; Hegermann, Jan; Miller, Rachel A.; Valguarnera, Ezequiel; Muriuki, Cecilia; Meens, Jochen; Nene, Vish; Naessens, Jan; Weber, Johann; et al.
Summary: M ycoplasma mycoides subsp. capri ( M mc ) and subsp. mycoides ( M mm ) are important ruminant pathogens worldwide causing diseases such as pleuropneumonia, mastitis and septicaemia. They express galactofuranose residues on their surface, but their role in pathogenesis has not yet been determined. The M . mycoides genomes contain up to several copies of the glf gene, which encodes an enzyme catalysing the last step in the synthesis of galactofuranose. We generated a deletion of the glf gene in a strain of M mc using genome transplantation and tandem repeat endonuclease coupled cleavage (TREC) with yeast as an intermediary host for the genome editing. As expected, the resulting YCp1.1‐Δ glf strain did not produce the galactofuranose‐containing glycans as shown by immunoblots and immuno‐electronmicroscopy employing a galactofuranose specific monoclonal antibody. The mutant lacking galactofuranose exhibited a decreased growth rate and a significantly enhanced adhesion to small ruminant cells. The mutant was also 'leaking' as revealed by a β‐galactosidase‐based assay employing a membrane impermeable substrate. These findings indicate that galactofuranose‐containing polysaccharides conceal adhesins and are important for membrane integrity. Unexpectedly, the mutant strain showed increased serum resistance. Abstract : To provide insights into the functional role of UDP‐galactopyranose mutase and capsular galactan in Mycoplasma mycoides, we made use of synthetic genomic tools such as genome transplantation and genome editing in yeast to create mutant strain YCpMmyc1.1‐Δ glf . Compared to its parental strain, YCpMmyc1.1‐Δ glf lacked galactofuranose‐containing galactan, showed a leaky membrane, had a reduced growth rate, exhibited increased adhesion to ruminant cells and showed increased serum resistance.